THE EFFECT OF USING PREVENTING NEWBORN BIRTH ASPHYXIA FOR PARTURIENT NURSING PRACTICE GUIDELINES ON THE KNOWLEDGE, PRACTICAL SKILLS, AND SATISFACTION AMONG NURSES, CHOMTHONG HOSPITAL - Dasurin, Apinya; Tanasirijiranont, Rattanaporn (Life Sciences and Environment Journal, 2024)
This quasi-experimental research aimed to compare the average scores of knowledges, practical skills, and nurse satisfaction before and after using the nursing practice guideline to prevent newborn birth asphyxia for parturients. The sample consisted of 11 nurses working in the delivery room at Chomthong Hospital. The research instrument was nursing practice guidelines for preventing birth hypoxia for the parturients. Data collecting instruments were personal information questionnaires, knowledge assessment forms, practical skills assessment forms, and satisfaction assessment forms for professional nurses. All research instruments were reviewed by three experts; an obstetrician, a pediatrician, and a head of the delivery room department which obtained a content validity index (CVI) of 1. Data collecting instruments were tested for reliability, and the results were 0.87, 0.76, and 0.94, respectively. Data analysis used descriptive statistics and the Wilcoxon Signed-Rank Test. The results showed that after the experiment, the sample group presented the average knowledge score and average practical skills score were higher than before the experiment significantly (p<.01), and an average nurse satisfaction score was higher than before the experiment significantly (p<.05). The results of this study should bring to provide knowledge and enhance the practical skills of nurses in caring for parturient to properly provide nursing care for them and newborns with the same nursing standard that it will help reduce the incidence of birth asphyxia.